Emission of CI Engine Using FeCl3 and Diethyl ether as Additives - P. Patnaik, P.; K.Acharya, S.; K.Mishra, S. (International Journal of Engineering and Technology, 2018)
Improving the performance of IC engine and reducing the toxic gases by applying the advance technology is the main key to safe guard the nation economy and health. The present investigation is to compare the emission of the single cylinder four-stroke diesel engine by adding proper additives ferric chloride (FeCl3) and diesel-diethyl ether (DEE) with diesel. The investigation defeats that Diesel-DEE15 combination has show the lowest HC and CO emissions except NO emission.
Keywords: diesel engine; ferric chloride; diethyl ether; nitrogen oxide